Antibacterial molecular sieve composite adsorption material and preparation method thereof

By preparing antibacterial molecular sieve composite adsorption materials, using lanthanum modified molecular sieve and solid-carrying ionic liquid, the problems of high desorption temperature and easy breeding of bacteria in existing materials are solved, and lower desorption temperature, higher adsorption performance and longer service life are achieved, and good antibacterial effects are achieved.

CN118874404BActive Publication Date: 2025-03-04GUANGDONG MICROEQUATION NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411094754.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-10
Publication Date
2025-03-04
Estimated Expiration
2044-08-10

AI Technical Summary

Technical Problem

The desorption temperature of existing molecular sieve composite adsorbent materials is too high, and bacteria are prone to breeding in humid environments, which poses health risks.

Method used

The antibacterial molecular sieve composite adsorption material is used. The preparation method includes mixing sodium water glass, composite molecular sieve and glyoxal, immersing it in a sulfuric acid solution, and preparing lanthanum modified molecular sieve through impregnation-calcination method to solid-carry ionic liquid to improve adsorption performance and antibacterial effect.

Benefits of technology

It reduces the desorption temperature of the molecular sieve, improves the adsorption performance, and uses chemical bonding to support ionic liquids, extends the service life of the material, and has good antibacterial properties, reducing health risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of adsorption materials, and in particular to an antibacterial molecular sieve composite adsorption material and a preparation method thereof. The antibacterial molecular sieve composite adsorption material comprises the following raw materials in weight percentage: 30-35% of sodium water glass, 3-5% of composite molecular sieve and 0.2-0.3% of glyoxal, with the balance being water. The molecular sieve is modified, rare earth elements are introduced into the molecular sieve, and ionic liquid is immobilized on the molecular sieve through chemical bond connection, thereby solving the problem of excessively high desorption temperature of the existing molecular sieve composite adsorption material. Meanwhile, the ionic liquid contains glucose units and quaternary ammonium structures, so that the composite adsorption material has good antibacterial performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of adsorption materials, and in particular to an antibacterial molecular sieve composite adsorption material and a preparation method thereof. Background Art

[0002] The control of environmental humidity is of great significance to improving living conditions, improving product quality and developing production technology. The adsorption rotary dehumidification system is widely used due to its large dehumidification capacity, high dehumidification efficiency, environmental protection and energy saving. Among them, the adsorption material of the rotary wheel is the decisive factor in the performance of the rotary dehumidification system.

[0003] Molecular sieve adsorbents, which are used as wheel adsorption materials, are widely used due to their excellent adsorption performance under high temperature and low humidity conditions. However, the desorption temperature of molecular sieves is as high as 250°C, which requires a large amount of heat energy, resulting in great restrictions on their use. At the same time, since the dehumidification wheel is in a humid environment for a long time, bacteria are inevitably bred. These bacteria are easily discharged with the dried air, posing certain health risks. Summary of the invention

[0004] The object of the present invention is to provide an antibacterial molecular sieve composite adsorption material and a preparation method thereof, which solves the problem of excessively high desorption temperature of the existing molecular sieve composite adsorption material and also has good antibacterial properties.

[0005] The object of the present invention can be achieved by the following technical scheme: A method for preparing an antibacterial molecular sieve composite adsorption material, comprising the following steps: Step S1: weighing the following raw materials in weight percentage: 30-35% sodium water glass, 3-5% composite molecular sieve and 0.2-0.3% glyoxal, the balance being water, and mixing the sodium water glass, the composite molecular sieve, glyoxal and water to prepare a mixed solution;

[0006] Step S2: immerse the glass fiber base cloth in the mixed solution for 5-10 minutes, dry it, and then immerse it in a sulfuric acid solution at a temperature of 50°C for 4-5 hours, the pH of the sulfuric acid solution is 6, wash it, and dry it to obtain an antibacterial molecular sieve composite adsorption material.

[0007] The composite molecular sieve is prepared by the following steps:

[0008] Step A1: acetyl bromide-α-D-glucose, chloroethanol and silver carbonate are mixed, and the mixture is reacted for 4-6 hours at a stirring rate of 100-120 rpm and a temperature of 35° C. to obtain intermediate 1; intermediate 1 is mixed with methanol, and the mixture is stirred at a stirring rate of 50-60 rpm and a temperature of 5° C., and sodium methoxide solution is added, and the mixture is reacted for 4-5 hours to obtain intermediate 2;

[0009] The dosage ratio of acetyl bromide-α-D-glucose, chloroethanol and silver carbonate is 2.8-3 g: 0.15-0.16 mol: 3.5-3.6 g, the molar concentration of sodium methoxide solution is 0.005 mol / L, and the dosage ratio of intermediate 1 and sodium methoxide solution is 1.2-1.4 g: 6-8 mL;

[0010] During the reaction, under the condition of silver carbonate as a catalyst, bromine in acetyl bromide-α-D-glucose reacts with hydroxyl in chloroethanol to obtain intermediate 1, and intermediate 1 is then hydrolyzed under the action of sodium methoxide solution to form hydroxyl to obtain intermediate 2;

[0011] Step A2: Mix intermediate 2 and N-vinyl imidazole, and react for 12-14 hours under nitrogen protection, at a stirring rate of 100-120 rpm and a temperature of 65°C to obtain intermediate 3; mix intermediate 3, sodium fluoroborate and deionized water, and react for 24 hours at a stirring rate of 100-120 rpm and a temperature of 70°C to obtain an ionic liquid;

[0012] The ratio of intermediate 2 to N-vinylimidazole is 3.4-3.6 g: 0.01-0.012 mol, and the ratio of intermediate 3 to sodium fluoroborate is 3-3.2 g: 1.1-1.2 g;

[0013] During the reaction, the chlorine in the intermediate 2 reacts with the imidazole in the N-vinyl imidazole to form an imidazolium structure to obtain the intermediate 3, and the intermediate 3 then undergoes an ion exchange reaction with sodium fluoroborate to obtain an ionic liquid;

[0014] Step A3: immersing the molecular sieve in a lanthanum nitrate solution, and adding an ammonia solution to adjust the pH value to 6, immersing for 50-60 minutes at a temperature of 60°C, drying, and calcining at 500°C for 2 hours to obtain a lanthanum-modified molecular sieve, mixing the lanthanum-modified molecular sieve, 3-mercaptopropyltriethoxysilane and toluene and ultrasonically dispersing for 15-20 minutes, reacting for 24 hours at a stirring rate of 120-180rpm and a temperature of 110°C, rotary evaporation, drying, filtering, mixing the filter cake, ionic liquid and acetonitrile, and reacting for 12-14 hours at a stirring rate of 120-180rpm and a temperature of 80°C to obtain a composite molecular sieve;

[0015] The mass concentration of lanthanum nitrate solution is 6%, the molar concentration of ammonia solution is 0.5 mol / L, the dosage ratio of molecular sieve and lanthanum nitrate solution is 1-1.2 g: 100-120 mL, and the dosage ratio of lanthanum modified molecular sieve, 3-mercaptopropyltriethoxysilane and ionic liquid is 2.2-2.3 g: 4-5 mL: 1.4-1.5 g;

[0016] During the reaction, an impregnation-calcination method is used. During the impregnation process, lanthanum is exchanged with ions in the molecular sieve, lanthanum is introduced into the molecular sieve, and then calcined to obtain a lanthanum-modified molecular sieve. The lanthanum-modified molecular sieve is then reacted and grafted with 3-mercaptopropyltriethoxysilane to introduce a mercapto group. The mercapto group then reacts with a double bond in the ionic liquid, and the ionic liquid is fixed on the lanthanum-modified molecular sieve through a chemical bond to obtain a composite molecular sieve.

[0017] The beneficial effects of the invention are as follows: the invention discloses an antibacterial molecular sieve composite adsorption material and a preparation method thereof, which solves the problem of the existing molecular sieve composite adsorption material having a high desorption temperature and has good antibacterial performance; the composite molecular sieve used in the composite adsorption material is subjected to an impregnation-calcination method, and lanthanum is exchanged with ions in the molecular sieve during the impregnation process, thereby modifying the molecular sieve and introducing lanthanum, and the introduction of lanthanum reduces the desorption activation energy of the molecular sieve, thereby reducing its desorption temperature, and the ionic liquid is immobilized by chemical bonds, and since the ionic liquid contains imidazolium and fluoroboric acid groups, these groups can increase the molecular sieve's adsorption of water after being immobilized on the molecular sieve with the ionic liquid, thereby improving the adsorption performance of the composite adsorption material, and since the ionic liquid contains glucose units, it can form a sugar cluster effect with bacteria, and then cooperate with quaternary ammonium groups to achieve a good antibacterial effect, and since the ionic liquid is immobilized on the molecular sieve by chemical bonds, the loss of the ionic liquid in repeated adsorption and desorption processes is reduced, thereby extending the service life of the composite adsorption material. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Example 1 A method for preparing an antibacterial molecular sieve composite adsorption material comprises the following steps: Step S1: weigh the following raw materials in weight percentage: 30% of commercially available Narmer sodium water glass, 3% of composite molecular sieve and 0.2% of glyoxal, and the balance is water, and mix the sodium water glass, composite molecular sieve, glyoxal and water to prepare a mixed solution;

[0020] Step S2: immersing the glass fiber base cloth in the mixed solution for 10 minutes, drying, and then immersing it in a sulfuric acid solution at a temperature of 50°C for 4 hours, the pH of the sulfuric acid solution is 6, washing, and drying to obtain an antibacterial molecular sieve composite adsorption material.

[0021] The composite molecular sieve is prepared by the following steps:

[0022] Step A1: acetyl bromide-α-D-glucose, chloroethanol and silver carbonate were mixed, and the mixture was reacted for 6 hours at a stirring rate of 120 rpm and a temperature of 35° C. to obtain intermediate 1; intermediate 1 was mixed with methanol, and the mixture was stirred at a stirring rate of 50 rpm and a temperature of 5° C., and sodium methoxide solution was added, and the mixture was reacted for 4 hours to obtain intermediate 2;

[0023] The dosage ratio of acetyl bromide-α-D-glucose, chloroethanol and silver carbonate is 3g:0.15-0.16mol:3.5g, the molar concentration of sodium methoxide solution is 0.005mol / L, and the dosage ratio of intermediate 1 and sodium methoxide solution is 1.4g:6mL;

[0024] Step A2: Mix intermediate 2 and N-vinyl imidazole, and react for 14 hours under nitrogen protection, at a stirring rate of 100 rpm and a temperature of 65°C to obtain intermediate 3; mix intermediate 3, sodium fluoroborate and deionized water, and react for 24 hours at a stirring rate of 120 rpm and a temperature of 70°C to obtain an ionic liquid;

[0025] The ratio of intermediate 2 to N-vinylimidazole is 3.6 g:0.01 mol, and the ratio of intermediate 3 to sodium fluoroborate is 3.2 g:1.1 g;

[0026] Step A3: immerse the commercially available Zhongliao 13X molecular sieve in a lanthanum nitrate solution, and add an ammonia solution to adjust the pH value to 6, immerse for 50 minutes at a temperature of 60°C, dry, and calcine at 500°C for 2 hours to obtain a lanthanum-modified molecular sieve, mix the lanthanum-modified molecular sieve, 3-mercaptopropyltriethoxysilane and toluene and ultrasonically disperse for 20 minutes, react for 24 hours at a stirring rate of 120 rpm and a temperature of 110°C, rotary evaporate, dry, filter, mix the filter cake, ionic liquid and acetonitrile, and react for 12 hours at a stirring rate of 180 rpm and a temperature of 80°C to obtain a composite molecular sieve;

[0027] The mass concentration of lanthanum nitrate solution is 6%, the molar concentration of ammonia solution is 0.5 mol / L, the dosage ratio of molecular sieve and lanthanum nitrate solution is 1.2 g:100 mL, and the dosage ratio of lanthanum modified molecular sieve, 3-mercaptopropyltriethoxysilane and ionic liquid is 2.3 g:5 mL:1.4 g.

[0028] Example 2 A method for preparing an antibacterial molecular sieve composite adsorption material comprises the following steps: Step S1: Weigh the following raw materials in weight percentage: 30% of commercially available Narmer sodium water glass, 3% of composite molecular sieve and 0.2% of glyoxal, the balance being water, and mix the sodium water glass, composite molecular sieve, glyoxal and water to prepare a mixed solution;

[0029] Step S2: immersing the glass fiber base cloth in the mixed solution for 5 minutes, drying, and then immersing it in a sulfuric acid solution at a temperature of 50°C for 4 hours, the pH of the sulfuric acid solution is 6, washing, and drying to obtain an antibacterial molecular sieve composite adsorption material.

[0030] The composite molecular sieve is prepared by the following steps:

[0031] Step A1: acetyl bromide-α-D-glucose, chloroethanol and silver carbonate were mixed, and the mixture was reacted at a stirring rate of 100 rpm and a temperature of 35° C. for 4 hours to obtain intermediate 1; intermediate 1 was mixed with methanol, and the mixture was stirred at a stirring rate of 50 rpm and a temperature of 5° C., and sodium methoxide solution was added thereto, and the mixture was reacted for 4 hours to obtain intermediate 2;

[0032] The dosage ratio of acetyl bromide-α-D-glucose, chloroethanol and silver carbonate is 2.8g:0.15-0.16mol:3.5g, the molar concentration of sodium methoxide solution is 0.005mol / L, and the dosage ratio of intermediate 1 and sodium methoxide solution is 1.2g:6mL;

[0033] Step A2: Mix intermediate 2 and N-vinyl imidazole, and react for 12 hours under nitrogen protection, at a stirring rate of 100 rpm and a temperature of 65°C to obtain intermediate 3; mix intermediate 3, sodium fluoroborate and deionized water, and react for 24 hours at a stirring rate of 100 rpm and a temperature of 70°C to obtain an ionic liquid;

[0034] The ratio of intermediate 2 to N-vinylimidazole is 3.4 g:0.01 mol, and the ratio of intermediate 3 to sodium fluoroborate is 3 g:1.1 g;

[0035] Step A3: immerse the commercially available Zhongliao 13X molecular sieve in a lanthanum nitrate solution, and add an ammonia solution to adjust the pH value to 6, immerse for 50 minutes at a temperature of 60°C, dry, and calcine at 500°C for 2 hours to obtain a lanthanum-modified molecular sieve, mix the lanthanum-modified molecular sieve, 3-mercaptopropyltriethoxysilane and toluene and ultrasonically disperse for 15 minutes, react for 24 hours at a stirring rate of 120 rpm and a temperature of 110°C, rotary evaporate, dry, filter, mix the filter cake, ionic liquid and acetonitrile, and react for 12 hours at a stirring rate of 120 rpm and a temperature of 80°C to obtain a composite molecular sieve;

[0036] The mass concentration of lanthanum nitrate solution is 6%, the molar concentration of ammonia solution is 0.5 mol / L, the dosage ratio of molecular sieve and lanthanum nitrate solution is 1 g:100 mL, and the dosage ratio of lanthanum modified molecular sieve, 3-mercaptopropyltriethoxysilane and ionic liquid is 2.2 g:4 mL:1.4 g.

[0037] Example 3 A method for preparing an antibacterial molecular sieve composite adsorption material comprises the following steps: Step S1: Weigh the following raw materials in weight percentage: 35% of commercially available Narmer sodium water glass, 5% of composite molecular sieve and 0.2% of glyoxal, and the balance is water, mix the sodium water glass, composite molecular sieve, glyoxal and water to prepare a mixed solution;

[0038] Step S2: immersing the glass fiber base cloth in the mixed solution for 10 minutes, drying, and then immersing it in a sulfuric acid solution at a temperature of 50°C for 4 hours, the pH of the sulfuric acid solution is 6, washing, and drying to obtain an antibacterial molecular sieve composite adsorption material.

[0039] The composite molecular sieve is prepared by the following steps:

[0040] Step A1: acetyl bromide-α-D-glucose, chloroethanol and silver carbonate were mixed, and the mixture was reacted at a stirring rate of 120 rpm and a temperature of 35° C. for 6 h to obtain intermediate 1; intermediate 1 was mixed with methanol, and the mixture was stirred at a stirring rate of 60 rpm and a temperature of 5° C., and sodium methoxide solution was added thereto, and the mixture was reacted for 5 h to obtain intermediate 2;

[0041] The ratio of acetyl bromide-α-D-glucose, chloroethanol and silver carbonate is 3g:0.16mol:3.6g, the molar concentration of sodium methoxide solution is 0.005mol / L, and the ratio of intermediate 1 and sodium methoxide solution is 1.4g:8mL;

[0042] Step A2: Mix intermediate 2 and N-vinyl imidazole, and react for 14 hours under nitrogen protection, at a stirring rate of 120 rpm and a temperature of 65°C to obtain intermediate 3; mix intermediate 3, sodium fluoroborate and deionized water, and react for 24 hours under a stirring rate of 120 rpm and a temperature of 70°C to obtain an ionic liquid;

[0043] The ratio of intermediate 2 to N-vinylimidazole is 3.6 g:0.012 mol, and the ratio of intermediate 3 to sodium fluoroborate is 3.2 g:1.2 g;

[0044] Step A3: immerse the commercially available Zhongliao 13X molecular sieve in a lanthanum nitrate solution, and add an ammonia solution to adjust the pH value to 6, immerse for 60 minutes at a temperature of 60°C, dry, and calcine at 500°C for 2 hours to obtain a lanthanum-modified molecular sieve, mix the lanthanum-modified molecular sieve, 3-mercaptopropyltriethoxysilane and toluene and ultrasonically disperse for 20 minutes, react for 24 hours at a stirring rate of 180 rpm and a temperature of 110°C, rotary evaporate, dry, filter, mix the filter cake, ionic liquid and acetonitrile, and react for 14 hours at a stirring rate of 180 rpm and a temperature of 80°C to obtain a composite molecular sieve;

[0045] The mass concentration of lanthanum nitrate solution is 6%, the molar concentration of ammonia solution is 0.5 mol / L, the dosage ratio of molecular sieve and lanthanum nitrate solution is 1.2 g:120 mL, and the dosage ratio of lanthanum modified molecular sieve, 3-mercaptopropyltriethoxysilane and ionic liquid is 2.3 g:5 mL:1.5 g.

[0046] Comparative Example 1 Compared with Example 3, this comparative example is different in that N-vinyl imidazole in the preparation process of the composite molecular sieve in Example 3 is replaced by N-methyl imidazole, and the other steps are the same.

[0047] Comparative Example 2 Compared with Example 3, this comparative example replaces the lanthanum modified molecular sieve in the preparation process of the composite molecular sieve in Example 3 with the commercially available Zhongliao 13X molecular sieve, and the other steps are the same.

[0048] Take the antibacterial molecular sieve composite adsorption materials prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2, cut them into 5mm×5mm samples, test their adsorption capacity under the conditions of room temperature, humidity of 90%, and adsorption time of 4h, and calculate their saturated adsorption percentage, and then test their desorption rate under the conditions of desorption time of 1h and temperature of 180°C. The antibacterial performance is tested by the flask oscillation method, and the sample is adsorbed for 4h at room temperature and humidity of 90%, and then desorbed for 1h at a temperature of 180°C. The above steps are used as cycle steps, and the sample is subjected to a cyclic adsorption and desorption experiment, the number of cycles is 30, and then the adsorption performance retention rate and the desorption performance retention rate at 180°C are calculated to evaluate its service life. The test results are shown in Table 1 below:

[0049] Table 1 Test results

[0050]

[0051] It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1 and Comparative Example 2, Comparative Example 1 replaces N-vinyl imidazole in the preparation process of the composite molecular sieve of Example 3 with N-methyl imidazole. Due to the lack of chemical bond connection, its performance decreases after repeated use. Comparative Example 2 replaces the lanthanum-modified molecular sieve in the preparation process of the composite molecular sieve of Example 3 with molecular sieve. Due to the lack of lanthanum modification, its desorption performance decreases.

[0052] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0053] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing an antibacterial molecular sieve composite adsorption material, characterized in that: The method comprises the following steps: Step S1: weighing the following raw materials in weight percentage: 30-35% sodium water glass, 3-5% composite molecular sieve and 0.2-0.3% glyoxal, with the balance being water, and mixing the sodium water glass, composite molecular sieve, glyoxal and water to prepare a mixed solution; Step S2: immersing the glass fiber base cloth in the mixed solution for 5-10 minutes, drying, and then immersing it in a sulfuric acid solution at a temperature of 50° C. for 4-5 hours, the pH value of the sulfuric acid solution is 6, washing, and drying to obtain an antibacterial molecular sieve composite adsorption material; The composite molecular sieve is prepared by the following steps: Step A1: acetyl bromide-α-D-glucose, chloroethanol and silver carbonate are mixed, and the mixture is reacted for 4-6 hours at a stirring rate of 100-120 rpm and a temperature of 35° C. to obtain intermediate 1; intermediate 1 is mixed with methanol, and the mixture is stirred at a stirring rate of 50-60 rpm and a temperature of 5° C., and sodium methoxide solution is added, and the mixture is reacted for 4-5 hours to obtain intermediate 2; Step A2: Mix intermediate 2 and N-vinyl imidazole, and react for 12-14 hours under nitrogen protection, at a stirring rate of 100-120 rpm and a temperature of 65°C to obtain intermediate 3; mix intermediate 3, sodium fluoroborate and deionized water, and react for 24 hours at a stirring rate of 100-120 rpm and a temperature of 70°C to obtain an ionic liquid; Step A3: Immerse the molecular sieve in a lanthanum nitrate solution, and add an ammonia solution to adjust the pH value to 6. At a temperature of 60°C, immerse for 50-60 minutes, dry, and calcine at 500°C for 2 hours to obtain a lanthanum-modified molecular sieve. Mix the lanthanum-modified molecular sieve, 3-mercaptopropyltriethoxysilane and toluene and ultrasonically disperse for 15-20 minutes. At a stirring rate of 120-180rpm and a temperature of 110°C, react for 24 hours, rotary evaporate, dry, and filter. Mix the filter cake, ionic liquid and acetonitrile, and react for 12-14 hours at a stirring rate of 120-180rpm and a temperature of 80°C to obtain a composite molecular sieve.

2. The method for preparing an antibacterial molecular sieve composite adsorption material according to claim 1, characterized in that: In step A1, the ratio of acetyl bromide-α-D-glucose, chloroethanol and silver carbonate is 2.8-3 g: 0.15-0.16 mol: 3.5-3.6 g, the molar concentration of the sodium methoxide solution is 0.005 mol / L, and the ratio of the intermediate 1 to the sodium methoxide solution is 1.2-1.4 g: 6-8 mL.

3. The method for preparing an antibacterial molecular sieve composite adsorption material according to claim 1, characterized in that: In step A2: the ratio of intermediate 2 to N-vinylimidazole is 3.4-3.6 g: 0.01-0.012 mol, and the ratio of intermediate 3 to sodium fluoroborate is 3-3.2 g: 1.1-1.2 g.

4. The method for preparing an antibacterial molecular sieve composite adsorption material according to claim 1, characterized in that: In step A3: the mass concentration of lanthanum nitrate solution is 6%, the molar concentration of ammonia solution is 0.5 mol / L, the molecular sieve and lanthanum nitrate solution are used in a ratio of 1-1.2 g: 100-120 mL, and the lanthanum modified molecular sieve, 3-mercaptopropyltriethoxysilane and ionic liquid are used in a ratio of 2.2-2.3 g: 4-5 mL: 1.4-1.5 g.

5. An antibacterial molecular sieve composite adsorption material, characterized in that: Prepared according to any one of the preparation methods described in claims 1-4.

Citation Information

Patent Citations

  • Rare-earth modified molecular-sieve dehumidification adsorbent paper sheet and preparation method thereof

    CN101972627A